Phonological Challenges in ESL Learning among Sinhala and Tamil Speakers in Colombo, Sri Lanka - Jawzi, Fathima Fazna; Abeywickrama, Rohan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2026)
This study looks into the phonological challenges that Sinhala and Tamil speaking ESL students in Colombo come across when learning English pronunciation. The study targets to examine the effect of first-language interference on English-speaking skill. Using a mixed-method approach, purposive sampling was used to select participants from a private language institute in Colombo. Quantitative data suggests that common errors such as improper replacement of consonants and the application of syllable-based rhythm. Qualitative results highlighted key factors such as first-language interference, learner anxiety, limited pronunciation-focused instruction, and sociocultural attitudes toward accent. Ultimately, this leads to the fact that these pronunciation difficulties contribute to errors that become a permanent habit in learners’ speech. The study offers pedagogical recommendations, which include contrastive teaching and clear practice of English stress patterns. It also recommends prioritizing pronunciation-focused training into ESL courses and increasing teacher training to address speech issues before they become permanent. Suggestions include improving ESL teaching in multilingual environments.